2015
DOI: 10.1007/jhep09(2015)133
|View full text |Cite
|
Sign up to set email alerts
|

Corner contributions to holographic entanglement entropy in non-conformal backgrounds

Abstract: We study corner contributions to holographic entanglement entropy in nonconformal backgrounds: a kink for D2-branes as well as a cone and two different types of crease for D4-branes. Unlike 2 + 1-dimensional CFTs, the corner contribution to the holographic entanglement entropy of D2-branes exhibits a power law behaviour rather than a logarithmic term. However, the logarithmic term emerges in the holographic entanglement entropy of D4-branes. We identify the logarithmic term for a cone in D4-brane background as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…(7.2) is a universal expression for general three-dimensional CFTs. It would also be interesting to explore how these expressions get modified in non-conformal theories, see e.g., [31,44,45]. Further, based on the properties of h n at small n, we have obtained that…”
Section: Discussionmentioning
confidence: 86%
“…(7.2) is a universal expression for general three-dimensional CFTs. It would also be interesting to explore how these expressions get modified in non-conformal theories, see e.g., [31,44,45]. Further, based on the properties of h n at small n, we have obtained that…”
Section: Discussionmentioning
confidence: 86%
“…where a (3) n (Ω) is a cutoff-independent function of the opening angle which has been extensively studied in the literature -e.g., for free fields in [15][16][17][18][19][20][21][22], for large-N vector models in [23], for holographic theories in [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], in interacting lattice models in [40][41][42][43][44][45], and for general CFTs in [46][47][48][49][50].…”
Section: Contentsmentioning
confidence: 99%
“…In particular recently it was shown that the constant σ is proportional to the central charge appearing in the two point function of the energy-momentum tensor as σ = π 2 24 C T , where this relation has some universal properties [17]. The existence and further generalizations of this universal ratio in more general cases is studied in several directions in [18][19][20][21][22][23][24].…”
Section: Jhep12(2015)082mentioning
confidence: 99%